Are we creating a new phenotype? Physiological barriers and ethical considerations in the treatment of hereditary transthyretin-amyloidosis - Maike F. Dohrn (BMC, 2021)
Abstract Hereditary transthyretin (TTR) amyloidosis (ATTRv) is an autosomal dominant, systemic disease transmitted by amyloidogenic mutations in the TTR gene. To prevent the otherwise fatal disease course, TTR stabilizers and mRNA silencing antisense drugs are currently approved treatment options. With 90% of the amyloidogenic protein produced by the liver, disease progression including polyneuropathy and cardiomyopathy, the two most prominent manifestations, can successfully be halted by hepatic drug targeting or—formerly—liver transplantation. Certain TTR variants, however, favor disease manifestations in the central nervous system (CNS) or eyes, which is mostly associated with TTR production in the choroid plexus and retina. These compartments cannot be sufficiently reached by any of the approved medications. From liver-transplanted patients, we have learned that with longer lifespans, such CNS manifestations become more relevant over time, even if the underlying TTR mutation is not primarily associated with such. Are we therefore creating a new phenotype? Prolonging life will most likely lead to a shift in the phenotypic spectrum, enabling manifestations like blindness, dementia, and cerebral hemorrhage to come out of the disease background. To overcome the first therapeutic limitation, the blood–brain barrier, we might be able to learn from other antisense drugs currently being used in research or even being approved for primary neurodegenerative CNS diseases like spinal muscular atrophy or Alzheimer’s disease. But what effects will unselective CNS TTR knock-down have considering its role in neuroprotection? A potential approach to overcome this second limitiation might be allele-specific targeting, which is, however, still far from clinical trials. Ethical standpoints underline the need for seamless data collection to enable more evidence-based decisions and for thoughtful consenting in research and clinical practice. We conclude that the current advances in treating ATTRv amyloidosis have become a meaningful example for mechanism-based treatment. With its great success in improving patient life spans, we will still have to face new challenges including shifts in the phenotype spectrum and the ongoing need for improved treatment precision. Further investigation is needed to address these closed barriers and open questions.